Application of BIM Technology in Building Mechanical and Electrical Engineering Modeling and Pipeline Inspection. Issue 2 (April 2021) - Hong, Cheng; Ming, Xia; Liu, Kai; Tu, Bin; Yu, Jiaxing
Abstract: With the development of China's urbanization process, the development of China's construction industry is in full swing. There are more and more large scale and special shaped buildings, and the electromechanical engineering and construction projects are more complex. The traditional architectural design and construction technology level could not meet the needs. The BIM Technology can build the whole building model completely, and carry out collision detection and analysis optimization of various specialties design stage, a series of problems can be avoided in the later stage. In this paper, Shanghai Baoshan project is taken as the research object, and the collision between the building model and the electromechanical pipeline is analyzed by using BIM software.